(untitled) (Journal of Academic Research, 2025)
Visual pollution is one of the most important problems that most cities in the developing world suffer from in general and in urban centres in Libya in particular. This study focused on revealing the most important aspects and factors affecting the aggravation of the problem of visual pollution in the municipality of Misurata in its various districts. As well, which of these factors are more influential in terms of distorting the general appearance and deteriorating the environmental quality of the municipality. The researchers in this study relied on the descriptive and quantitative approach, by relying on observation and field study in the study areas districts. As well as, distributing a questionnaire randomly using a cluster sampling method on a sample size of (100) people from the population of the municipality in its various districts. The study concluded that there are 17 factors that contributed to the emergence of this problem in the municipality at different levels, which contributed to the aggravation of this problem in the districts of the municipality, and reached a set of recommendations to overcome and reduce this issue.